Combination therapy with anti-DR5 antibody and tamoxifen for triple negative breast cancer - Kim, Hyunki (Landes Bioscience, 2014)
TRA-8, a monoclonal antibody targeting death receptor, has demonstrated high therapeutic effect for triple negative breast cancer (TNBC) in preclinical models. Tamoxifen, the standard of care for ERα-positive breast cancer, induces apoptosis via ERβ, which commonly presents in TNBC cells. The current study investigates the combination effects of TRA-8 and tamoxifen for TNBC. In vitro assays were implemented with two ERβ-positive TNBC cell lines, SUM159 and 2LMP, and in vivo therapy studies were followed using orthotopic breast tumor mouse models. IC(50) of tamoxifen for SUM159 and 2LMP were 29 μM and 38 μM, respectively. Synergy between TRA-8 (0–1000 ng/mL) and tamoxifen (20 μM) was observed for both the cell lines. Tamoxifen (400 mg/kg diet) markedly suppressed the growth of SUM159 tumors for 6 weeks after therapy initiation, but it did not induce antitumor effect for 2LMP tumors. TRA-8 (0.1 mg, weekly, i.p.) successfully arrested the growth of both SUM159 and 2LMP tumors during therapy, but an antagonistic effect was observed when tamoxifen was combined. TRA-8 uptake into tumors was not changed by tamoxifen treatment. Histological analysis confirmed that caspase-3 activation induced by TRA-8 was significantly decreased when tamoxifen was used in combination. In conclusion, our findings suggest that the combined use of TRA-8 and tamoxifen may cause antagonistic effects for TNBC patients.